Lifestyle factors associated with cognitive functioning in breast cancer survivors. Issue 6 (29th July 2014) - Hartman, Sheri J.; Marinac, Catherine R.; Natarajan, Loki; Patterson, Ruth E.
Abstract Objective Weight, physical activity, and sleep are modifiable lifestyle factors that impact cognitive functioning in noncancer populations but have yet to be examined in cancer survivors. The aim of the study was to assess the relationship of obesity, physical activity, and sleep, with cognitive functioning among breast cancer survivors. Methods Participants were 136 early‐stage postmenopausal breast cancer survivors who completed an assessment of neuropsychological testing, height, weight, physical activity, and sleep. Linear regression models examined the associations of the seven neuropsychological domains with obesity, physical activity, and sleep. Logistic regression models examined odd of impairment in each domain. All models controlled for breast cancer treatment variables and relevant demographic and clinical variables. Results Obese participants had significantly worse performance (β = −5.04, standard error (SE) = 2.53) and were almost three times more likely to be impaired (odds ratio (OR) = 2.87; 95% CI: 1.02–8.10) on the Information processing domain. The highest tertile of physical activity was significantly related to better performance on the executive functioning domain (β = 5.13, SE = 2.42) and attention domain (β = 4.26, SE = 2.07). The middle tertile of physical activity was significantly related to better performance (β = 9.00, SE = 3.09) and decreased odds of impairment (OR = 0.89, 95% CI: 0.07–0.91) on the visual–spatial domain. More hours of sleep per night was significantly associated with better performance (β = 2.69, SE = 0.98) and decreased odds of impairment (OR = 0.52; 95% CI: 0.33–0.82) on the verbal functioning domain. Conclusions These findings suggest that obesity, physical activity, and sleep are related to cognitive functioning among breast cancer survivors and have potential to be intervention targets to improve cognitive functioning. Copyright © 2014 John Wiley & Sons, Ltd.